2016
DOI: 10.1177/0020764016629694
|View full text |Cite
|
Sign up to set email alerts
|

Perceived insecurity, mental health and urbanization: Results from a multicentric study

Abstract: Our findings confirm the presence of a common sense of perceived uncertainty among our sample. Such attitude toward life can have a detrimental impact on patients' psychological and physical well-being, contributing to high levels of distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…A caveat in the analysis needs to be noted before we conclude. Although we observed a direct association between worries and psychological distress, it is also likely that higher levels of psychological distress can worsen attitudes about life and amplify worries [48]. The relationship between worries and psychological distress requires further investigation to disentangle how worries may in uence psychological distress and vice versa.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A caveat in the analysis needs to be noted before we conclude. Although we observed a direct association between worries and psychological distress, it is also likely that higher levels of psychological distress can worsen attitudes about life and amplify worries [48]. The relationship between worries and psychological distress requires further investigation to disentangle how worries may in uence psychological distress and vice versa.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
“…Micro-worries refer to potential problems of individuals and their circle, whereas macro-worries are associated with problems in broader social contexts, such as race/ethnicity, social class, nation state, or even the world [47]. Studies have documented the detrimental impact of micro-worries on psychological well-being, leading to higher levels of distress [48]. Macro-worries, on the other hand, are not associated with mental health [47].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Many studies have shown that living in urban settings is associated with higher perception of insecurity and personal risk of violence in general populations as well as in people with schizophrenia. 12,13 Insecurity, violence, trauma, and disorganized neighborhood may all reduce social support/interaction and affect wellbeing and mental health. 14 Social interactions and support may be also reduced by social stigma and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…However, these offer a quite limited picture of what occurred. The last in order of time concerns the results of a multicenter study on perceived insecurity, mental health and urbanization without specific information on Trieste (Luciano et al, 2016). A multicenter study on determinants of quality of life in users across Europe does not say much about the specificity of Trieste, except paradoxically that the Trieste unit is the one whose users score the lowest on the human rights scale (Killaspy et al, 2016).…”
Section: Scarce Attention To Measuring the Results Of Change With Scimentioning
confidence: 99%